Navigating translational ecology: creating opportunities for scientist participation. Issue 10 (1st December 2017) - Hallett, Lauren M; Morelli, Toni Lyn; Gerber, Leah R; Moritz, Max A; Schwartz, Mark W; Stephenson, Nathan L; Tank, Jennifer L; Williamson, Matthew A; Woodhouse, Connie A
Abstract : Interest in translational ecology (TE) – a research approach that yields useful scientific outcomes through ongoing collaboration between scientists and stakeholders – is growing among both of these groups. Translational ecology brings together participants from different cultures and with different professional incentives. We address ways to cultivate a culture of TE, such as investing time in understanding one another's decision context and incentives, and outline common entry points to translational research, such as working through boundary organizations, building place‐based research programs, and being open to opportunities as they arise. We also highlight common institutional constraints on scientists and practitioners, and ways in which collaborative research can overcome these limitations, emphasizing considerations for navigating TE within current institutional frameworks, but also pointing out ways in which institutions are evolving to facilitate translational research approaches.